Multimodal exercise ameliorates exercise responses and body composition in head and neck cancer patients receiving chemotherapy - Yen, Chia-Jui; Hung, Ching-Hsia; Kao, Chung-Lan; Tsai, Wei-Ming; Chan, Shih-Hung; Cheng, Hui-Ching; Jheng, Wan-Ting; Lu, Yan-Jhen; Tsai, Kun-Ling (Supportive care in cancer, 2019)
Background Studies have found that many chemotherapy drugs will produce multiple side effects and complications in cancer patients, especially in the case of the cardiovascular disease. This study was intended to investigate whether the exercise training intervention could improve the body composition and exercise responses of patients with head and neck (H&N) cancer who are receiving chemotherapy. Methods This is a randomized controlled trial. Eighty-four H&N patients were assigned to sedentary group or exercise group. The data were collected pretraining and posttraining, where the body composition, heart rate (HR), blood pressure (BP), rate-pressure product (RPP), and exercise capacity were measured. Results Our data reported that body weight and body mass index were decreased after 8 weeks of chemotherapy in the sedentary group but not in the exercise group. The decreased visceral fat and the increased skeletal muscle rate had been found in the exercise group after 8 weeks of training. In addition, in the exercise group, the HR, HR recovery, BP, BP recovery, RPP, and minutes walking distance were better than the sedentary group. Results from this study suggested exercise training significantly improved exercise responses and body composition. Conclusion These findings suggested that exercise can help to promote cardiopulmonary fitness and exercise capacity for H&N cancer patients undergoing chemotherapy.